Membentuk Karakter Peserta Didik dengan Pendekatan Deep Learning - AL AKHYAR, DWIKI (MGMP PAI SMP BINTAN, 2024)
This study aims to describe the efforts to cultivate leadership character in students through a deep learning approach. The method used in this study is library research with a qualitative approach. For research instruments, the researcher employs observation and documentation, while data analysis is conducted qualitatively. The results indicate that the identified leadership values include innovative attitudes, creativity, justice, wisdom, simplicity, consensus-building, and honesty. These values reflect the qualities exemplified by the Prophet Muhammad Shallallahu Alaihi Wasallam, such as siddiq (truthfulness), amanah (trustworthiness), tabligh (communication), and fathonah (intelligence). Deep learning can be implemented through substantive and reflective approaches. Additionally, this process should be synergized with the roles of Islamic educational institutions, including family, madrasah, and society.